KOPERASI SEBAGAI WADAH DALAM PENGEMBANGAN USAHA MIKRO, KECIL, DAN MENENGAH PADA SENTRA BUDIDAYA JAMUR DI DESA GENTING KABUPATEN SEMARANG - Dimas Adi Nugroho*, Srie Wiletno, Siti Mahmudah (Diponegoro Law Journal, 2014)
Usaha Mikro, Kecil, dan Menengah (UMKM) is one of the backbone of the economy in Indonesia. One of the factors that make UMKM have hold up is their business prospects. But in its development, UMKM have not been able to increase their potential to the maximum. As in the case of UMKM jamur in the village of Genting that have good prospects from their mushroom cultivation business , but do not have the appropriate container in its development efforts. Cooperative is an organization that is right for the development of UMKM jamur in the village of Genting. It can be seen based on the purpose and function of the cooperation. In addition, the cooperative is a means for the government in carrying out its role for the empowerment and development of UMKM. Keywords: Cooperative, UMKM, Mushroom Cultivation